Gynomorphic Mandible Morphology in the Dobsonfly, Corydalus cornutus - Bowles, David E. (University of Wisconsin Library, 2007)

(untitled)
Two aberrant males of Corydalus cornutus (L.) (Insecta: Megaloptera), which exhibit unusually short mandibles with discrete dentition, are recorded from a locality in Missouri. Morphological details of the specimens, as well as implications for the overall morphological variation of the genus and species are discussed. The term gynomorphic is suggested as the best descriptor of this case, given that little explanatory information is available to classify these specimens as true gynandromorphs.